The Influence Of Digital Marketing On Nero Homestay Rental Decision Making In Tanah Kuning - Sadana, Raditya; Kadir, Nuraeni; Jusni, Jusni (SEIKO : Journal of Management & Business, 2023)
This study looks at how consumer decisions about what to buy at Tanah Kuning's Nero Homestay are influenced by social media and digital marketing. In this study, survey approaches are combined with quantitative methodologies. 385 individuals provided information via a questionnaire. Descriptive analysis and the structural equation model (SEM) were used in the data analysis, which was done with SPSS and SmartPLS. The study's findings demonstrate that, at Nero Homestay, social media and digital marketing significantly and favorably affect customers' decisions to buy. This means that the more effectively Nero Homestay uses social media and digital marketing, the more likely it is that customers will make a purchase. Keywords: digital marketing, social media marketing, and decisions purchase.